Past Looking : Historical Imagination and the Rhetoric of the Image - Holly, Michael Ann (Book collections on Project MUSE., 1996)
Michael Ann Holly asserts that historical interpretation of the pictorial arts is always the intellectual product of a dynamic exchange between past and present. Recent theory emphasizes the subjectivity of the historian and the ways in which any interpretation betrays the presence of an interpreter. In Past Looking, she challenges that view, arguing that historical objects of representational art are actively engaged in prefiguring the kinds of histories that can be written about them. Holly directs her attention to early modern works of visual art and their rhetorical roles in legislating the kind of tales told bout them by a few classic cultural commentaries of the nineteenth and twentieth centuries: Burckhardt's synchronic vision of the Italian Renaissance, Wölfflin's exemplification of the Baroque, Schapiro's and Freud's dispute over the meanings of Leonardo's art, and Panofsky's exegesis of the disguised symbolism of Northern Renaissance painting.